In situ observations of an active MoS2 model hydrodesulfurization catalyst - Rik V. Mom (Nature Portfolio, 2019)
Although hydrodesulfurization is a key process in the chemical industry, a deep understanding of the catalyst structure under real reaction conditions is lacking. Here, the authors combine theoretical calculations with high-pressure scanning tunneling microscopy to elucidate the MoS2 catalyst structure under reaction conditions.